Monitoring oriental fruit moth (Lepidoptera: Tortricidae) with the Ajar bait trap in orchards under mating disruption. (8th May 2013) - Knight, A.; Basoalto, E.; Hilton, R.; Molinari, F.; Zoller, B.; Hansen, R.; Krawczyk, G.; Hull, L.
Abstract: Studies in Oregon, California, Pennsylvania and Italy evaluated the relative performance of the Ajar trap compared with several other traps for the capture of Grapholita molesta (Busck), in pome and stone fruit orchards treated with sex pheromone dispensers for mating disruption. The Ajar is a delta‐shaped trap with a screened jar filled with an aqueous terpinyl acetate plus brown sugar bait solution (TAS) that opens inside the trap and is surrounded by a sticky liner. The TAS‐baited Ajar trap was evaluated with and without the addition of a sex pheromone lure and compared with a delta trap baited with a sex pheromone lure and a bucket trap filled with the TAS bait. Although the Ajar trap had a 90% lower evaporation of the TAS bait than the bucket trap, both of them caught similar numbers in the majority of the field tests of both sexes of G. molesta . The addition of the sex pheromone lure did not increase moth catches by the TAS‐baited Ajar trap. The TAS‐baited Ajar trap caught significantly greater numbers of moths than the sex pheromone‐baited delta trap in 18 of the 20 orchards. Few hymenopterans were caught in orange TAS‐baited Ajar traps, but the catch of flies and other moths relative to the target pest remained high. Flight tunnel and field tests evaluated the effect of several screen designs on the catches of G. molesta and non‐target species. All exclusion devices significantly reduced the catch of larger moths. However, designs that did not reduce the catch of male G. molesta did not reduce the catch of muscid flies. Exclusion devices with openings <7.0 mm significantly reduced the catch of female G. molesta . The addition of ( E )‐ β ‐farnesene, ( E )‐ β ‐ocimene or butyl hexanoate septa lures to TAS‐baited Ajar traps significantly increased total moth catch. The addition of ( E )‐ β ‐ocimene also significantly increased female moth catch.